Coordinated control strategy for HVDC frequency controllers in multi-area asynchronous grid - Jianxiong Lei; Rongzhao Yang; Weixiong Wu; Weicheng Lu; Weike Mo (International Journal of Electrical Power & Energy Systems)
Due to the complexity and fragility of large-scale synchronous grids, utilizing High Voltage Direct Current (HVDC) links for interconnecting asynchronous grids has emerged as a significant trend in modern power systems. To address the issues of limited mutual support capability between regional grids and the declining inertia and primary frequency modulation capability of regional grids with increasing penetration of renewable energy, a coordinated control strategy for HVDC frequency controllers in multi-area asynchronous grids is proposed. Firstly, a frequency control model of multi-area asynchronous grids interconnected by HVDC is constructed, and the dynamic frequency response equations of the system are obtained. Then, considering the types of disturbances in the multi-area system comprehensively, the quantitative analysis of the steady-state frequency deviation(SSFD), and whether the rectifier and inverter sides of each regional grid participate in frequency regulation, the coordinated control strategy for HVDC frequency controllers is obtained based on an exhaustive search algorithm. Finally, the impact of control parameters in the HVDC frequency controller on system frequency stability is analyzed utilizing the state-space model. Considering the results of the stability analysis, an optimization methodology for tuning the droop parameters of the frequency controller is proposed, employing an exhaustive search algorithm. The effectiveness and feasibility of the proposed control strategy and droop parameter tuning method are verified through numerical simulations.